A study of students’ motivation in using the mobile arc welding learning app - Najwa Rusli, Farhatun; Zulkifli, Abdul Nasir; Saad, Mohd. Nizam; Md Yussop, Yussalita (2019)
Welding is an introductory core subject that is taught in every mechanical engineering programs at all polytechnics in Malaysia. Normally students will learn the theoretical concepts of welding in the class followed by instruction-based training in the workshop. However, students have difficulty to follow everything that has been taught in the class in a limited time. Welding is dangerous for beginners and the welding environments are harmful and injurious to the health. In this paper, we introduce Mobile Arc Welding Learning (MAWL) app, a new approach for learning arc welding that incorporates mobile technology and enhanced with augmented reality (AR). The aim of this app is to enhance the contents used in arc welding learning materials used in the conventional learning by visualizing the information through the use of text, images, videos and 3D models. The MAWL app covers topics related to safety in welding, components of welding and steps in welding. The students can use the app to learn about welding on their own anytime and anywhere. The potential of using the MAWL app for welding learning among the polytechnic students has been investigated, specifically focusing on ease of use, learn ability, satisfaction, usefulness, motivation and engagement. The results of the evaluation indicate that the users strongly agreed on ease of use, learn ability, satisfaction, usefulness and motivation, while they agreed on engagement. These prove that the MAWL app has the potential to contribute to students’ welding learning through interactive and accessible information that satisfies them